ANALISIS STATUS KEBERLANJUTAN AGROFORESTRI KOPI: KASUS KELOMPOK TANI HUTAN KEMASYARAKATAN DI KAWASAN HUTAN LINDUNG BUKIT DAUN KABUPATEN LEBONG PROVINSI BENGKULU - Jesika Martini; Septri Widiono; Reswita Reswita; Yayat Hidayat (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
Sustainability is an important aspect in forest resource management that determines ecological balance, economic welfare, and long-term social sustainability. This study aims to analyze the sustainability status of coffee agroforestry in the Community Forest (HKm) scheme in the Bukit Daun Protection Forest Area, Lebong Regency, Bengkulu Province, based on five dimensions of sustainability (ecological, economic, social, technological, and institutional). Using the MCDA VIKOR approach to determine sustainability status, and PCA to identify dominant indicators. Data were obtained from 182 respondents who are members of 9 GKTH, and weighting by 4 experts. The results show that GKTH Telaga 7 Warna and Bioa Sengok are categorized as highly sustainable, two GKTH are quite sustainable, and five others are unsustainable. The dominant indicators that influence sustainability status are Production Reliability based on plant diversity, agroforestry efficiency and capacity strengthening based on HKm legality, knowledge capacity and social participation of HKm farmers, independence and local-based technological innovation, and the effectiveness of governance and cohesiveness of KTH members.